The Analysis of Code Switching in EFL Students’ Online Presentation at University - Zahra, Annisa Fatimatus; Atmowardoyo, Haryanto; Salija, Kisman (Har Press Indonesia, 2023)
Code-switching is a phenomenon of language exchange between one language and another which is often found in the communication of bilingual students, especially in EFL students. In this study, the researcher focuses to determine the types of code switching in EFL students’ online presentations, factors that influence code-switching in students’ online presentations and functions of code-switching in EFL students’ online presentations. This study applied a qualitative method by applying a case study. This research was conducted at Makassar State University. The subjects of this study were twenty-one students in the first semester of the postgraduate program whose selected by purposive sampling technique. This research was obtained by using observation and interviews as instruments. The results of this study indicate that three types of code-switching appear in EFL students’ online presentations, namely intra-sentential code-switching, extra-sentential or tag switching, and inter-sentential code-switching. Then, the factors that influence code-switching occur in students' online presentations are the interlocutor factor, physical situation, the topic of discourse, regional factor, and also lack of vocabulary. Furthermore, there are four functions of code-switching by EFL students during online presentations providing the keywords, explaining the material clearly, solving nervousness, and reducing tension.